THE ROLE OF BIG DATA IN MANAGERIAL ACCOUNTING DECISION-MAKING: A LITERATURE REVIEW - Linatul Uyun (CV. Fahr Publishing, 2025)
This study explores the transformative role of Big Data Analytics (BDA) in managerial accounting decision-making, addressing a critical need to understand how data-driven tools reshape accounting processes and strategic outcomes. The primary objective is to synthesize recent literature (2015–2025) to identify key themes, capabilities, and barriers in leveraging BDA for internal accounting decisions. A systematic literature review method was employed, selecting 40 peer-reviewed articles from databases such as Scopus, ScienceDirect, and Google Scholar. Thematic content analysis was used to extract patterns across four major themes: analytics capability, decision-making impact, organizational readiness, and adoption barriers. Results show that while BDA significantly enhances forecasting accuracy, responsiveness, and strategic relevance, its effective implementation is hindered by skill gaps among accounting professionals, fragmented systems, and lack of cultural readiness. The novelty of this research lies in its focus on the mechanism by which BDA influences managerial accounting workflows, especially through the integration of human competencies, business intelligence systems, and contextual sectoral differences. Unlike prior studies that emphasize tools and technologies, this paper highlights the evolving role of accountants as analytical decision-support agents. Additionally, the study proposes a conceptual foundation for future empirical research and offers practical insights for educators and firms aiming to modernize accounting roles in the digital age. In conclusion, integrating BDA into managerial accounting is not solely a technological upgrade—it requires strategic alignment, upskilling, and organizational transformation to achieve decision-making excellence.